Can participatory systems modeling of food value chains improve food and nutrition security under climate change? - Nicholson, Charles F.; Mason-D'Croz, Daniel; Thornton, Philip K.; Phillips, E.L.; Cramer, Laura K.; Garrett, James L.; Gómez, M.I.; Herrero, Mario; Jones, A.D.; Kopainsky, B.; Monterrosa, Eva; Parsons, D.; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This is a summary of workshop discussions at the Global Food Security Conference at KU Leuven in Belgium. This was presented as part of a session on modeling approaches to food security analysis.